Efficacy, Safety and Tolerability of Dapagliflozin and Teneligliptin Fixeddose Combination in Patients with Type 2 Diabetes Mellitus Inadequately Controlled on Metformin Monotherapy: A Double Blind, Four-arm, Randomized Phase 3 Clinical Study - Khandelwal, Vipul; Naskar, Arindam; Borthakur, Swapna; Borulkar, Rahee; Jadhav, Mayur; Bhushan, Sumit; Choudhari, Sanjay; Patil, Saiprasad; Barkate, Hanmant (Archives of Clinical and Biomedical Research, 2025)
Introduction: The failure of metformin monotherapy and intolerance to metformin combinations have necessitated the evaluation of various fixeddose combinations (FDC) of oral hypoglycaemic agents. The newer FDCs belong to the class of Sodium-Glucose Cotransporter Type 2 (SGLT2) inhibitors and Dipeptidyl Peptidase-4 Inhibitor (DPP4) inhibitors. In this study the efficacy and safety of the FDC of Dapagliflozin and Teneligliptin in Indian Type 2 Diabetes Mellitus (T2DM) patients were evaluated. Methods: This multicentric, randomized, prospective, double-blind, fourarm, phase III study included inadequately controlled T2DM patients on metformin monotherapy (≥ 1500 mg/day). Subjects were randomized into four groups and received either the FDC or the monotherapy of Dapagliflozin and Teneligliptin over 24 weeks. The study endpoints included improvement in glycaemic parameters, reduced body weight, and occurrence of adverse events. Results: FDC group of Dapagliflozin 5/10mg + Teneligliptin 20mg demonstrated a significant reduction in HbA1C by 1.5% (P < 0.0001) compared to the individual groups of Dapagliflozin (-1.1%) & Teneligliptin (-0.9%). A similar trend was observed for Fasting Plasma Glucose (FPG) and Postprandial Plasma Glucose (PPG) with the FDC groups (P < 0.0001). The mean reduction in body weight from baseline to week 24 was prominent in the Dapagliflozin 10mg (-2.16 kg) group. When compared amongst the groups, weight reduction in Dapagliflozin 10mg + Teneligliptin 20mg group was significantly more than Dapagliflozin 5mg + Teneligliptin 20mg and Teneligliptin 20mg (P <0.01) monotherapy. The reported adverse events were mild and uneventful. Conclusion: The FDC of Dapagliflozin and Teneligliptin effectively improved glycaemic parameters and body weight in T2DM patients. The FDC of Dapagliflozin and Teneligliptin based on the current evidence can be considered for T2DM patients inadequately controlled on metformin monotherapy.